Utilization of Antenatal care services in present pregnancy among the women attending in a Teaching Hospital for delivery - Thapa, Meena; Yadav, S; Bhujel, K (Nepal Journal of Obstetrics and Gynaecology, 2016)
Aims: To study attendance of antenatal care services during present pregnancy by pregnant women coming for delivery in a teaching hospital of Kathmandu and to analyze the impact of educational status, age group, gravida (number of pregnancy) and occupation of the women on antenatal care service utilization. Methods: Uncomplicated, term pregnant women who came for delivery in labour or for induction of labour or elective cesarean section were interviewed using semi-structured questionnaire. Results: Six hundred and four pregnant women were studied. Antenatal care coverage in studied population was found to be 94.8% with adequate (four) antenatal care visits in 83.4%. Women belonged to 20 to 30 years of age group and higher education status had higher rate of antenatal care attendance where as women who belonged to labor class (daily earner) had significantly lower rate of adequate antenatal care attendance. Number of pregnancy (gravida) of the women did not show association with rate of antenatal care attendance. Conclusions: Over all antenatal care attendance in this study is very high. Women of 20 to 30 years of age and higher education status had positive effect on antenatal care attendance, where as women who were daily earner or labour had higher rate of failure to attend antenatal care visits.